Obesity, eating disorders and the media - Karin, Eli; Ulijaszek, Stanley J. (Ashgate, 2014)
How do the media represent obesity and eating disorders? How are these representations related to one another? And how do the news media select which scientific findings and policy decisions to report? Multi-disciplinary in approach, Obesity, Eating Disorders and the Media presents critical new perspectives on media representations of obesity and eating disorders, with analyses of print, online, and televisual media framings.